The best of Adam Sharp - Simsion, Graeme C. (St. Martin's Press, 2017)
"On the cusp of turning fifty, Adam Sharp likes his life. He's happy with his partner Claire, he excels in music trivia at quiz night at the local pub, he looks after his mother, and he does the occasional consulting job in IT. But he can never quite shake off his nostalgia for what might have been: his blazing affair more than twenty years ago with an intelligent and strong-willed actress named Angelina Brown who taught him for the first time what it means to find--and then lose--love. How different might his life have been if he hadn't let her walk away? And then, out of nowhere, from the other side of the world, Angelina gets in touch. What does she want? Does Adam dare to live dangerously?"--